The Integrated Sexual and Reproductive Health Learning Model for Children with Special Needs in West Java, East Java and North Sumatra Province - Fatimatuzzahra, Ana; Rochyadi, Endang; Akhlan, Riksma Nurhami; Ratnengsih, Een (Department of Special Education, 2024)
The implementation of Sexual and Reproductive Health (SRH) Education in Special Schools is starting to get special attention. Having a Special Program designed for Children with Special Needs is an important factor that SRH’s material must be taught in Special Schools. However, in reality this Special Program is not comprehensive in delivering SRH’s material, so that it is widely spread in several other subjects such as Sciences, Religion, Character, Sports and Citizenship Education. The research aims to see the implementation of the SRH learning model in an integrated approach with those subjects that conducted by teachers in West Java, East Java and North Sumatra. Research method uses the action research approach which focuses on four stages of research namely planning, action, observation and reflection. The subjects of the study are 41 teachers from three provinces who teach Sciences, Religion, Character, Sports, Citizenship Education and Special Program. The results of the study show that the integrated SRH model through special programs and subjects can be implemented properly. This can be shown from the number of teachers as many as 41 people who implement this integrated SRH learning model showing a presentation rate of 60.97% with good implementation results. This result calculated from total teachers spread across seven schools in West Java, East Java and North Sumatra.